Upaya Preventif Kepolisian dalam Menanggulangi KasusTindak Pidana Kekerasan dalam RumahTangga (KDRT) terhadap Keluarga (Studi Kasus di Polresta Tanjungpinang, Kepulauan Riau) - Diah Ratna Karina; Polter Gultom (Neolectura, 2026)
Domestic Violence (DV) is a profound social issue with significant impacts on victims, who are often trapped in a cycle of repeated abuse. The police, as the frontline in law enforcement, play a crucial role in providing protection for victims and addressing DV through preventive measures. This study analyzes the preventive efforts made by the Tanjungpinang Police in combating DV, focusing on the implemented prevention policies and the challenges faced. The research method used is a normative juridical approach with case studies and interviews with police officers and related institutions. The findings show that the Tanjungpinang Police have implemented various programs such as legal awareness campaigns, security patrols, and collaboration with women and children’s protection agencies. However, significant challenges remain related to limited resources, low legal awareness in the community, and the patriarchal culture that hinders the effectiveness of preventive efforts. Recommendations include enhancing police capacity, strengthening collaboration with related institutions, and utilizing technology to facilitate DV reporting. This study contributes to the development of police policies for more effective DV prevention.